Economic integration: - Halili, Nijazi; Aziz Rexhepi,; Besarta Rexhepi,; Arbresha Meha, (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
In this scientific paper we have presented how the European Integration process gives results so that the level of economic development is approximately comparable between different countries. The economic structure should be, if possible, the complementary structure of production and the market between different countries. The basic economic goals are to advance the development of economic activities between member states, the permanent and balanced expansion of the economy, greater economic stability and the improvement of living standards and the strengthening of economic relations between member states. The realization of the set goals is realized through: elimination of barriers and ensuring the free movement of labor, the circulation of capital and services, the establishment of a common customs tariff for EEC countries. It is considered that the reform in accordance with the standards of the European Union, is one of the most effective measures for the acceleration and successful transition of the transition process and individually advancement in the process of European integration.